The Implementation of Cloze Procedure Technique in Enhancing Students' Reading Ability - Hadijah; Amzah Selle; Mujahidah (Inspiring: English Education Journal, 2020)
This research is intended to investigate the effect of cloze procedure technique in teaching reading ability to the second-grade students of Senior High School SMAN 3 Pinrang. The study’s object is the class from XI MIPA 1 which consists of 32 students. The study is conducted through two cycles with each cycle consisted of three meeting. While the score of the students in cycle 2 is higher that cycle 1. Close procedure technique is effective in teaching reading ability. Almost all of the students are able to answer the question. It also can be concluded that the students who were taught by using close procedure technique have a better performance than those who were not. The study finds that the students’ knowledge about reading was good. It covered students’ vocabulary and grammar was good. They also fair hasty in deliver their reading.